Occupational employment projections to 2008. - Braddock, Douglas (Monthly Labor Review)
Part of a special issue on the Bureau of Labor Statistics' projections for employment between 1998 and 2008. Occupational implications of projected industry trends for employment are examined. Professional managers, technicians, and service, marketing, and sales personnel are expected to increase their share of total employment over the next decade, whereas administrative support; precision production, craft, and repair workers; and fabricators, operators, and laborers will experience relative declines. Computer and health-related jobs dominate the list of fastest growing occupations. Because of their size, some occupations, such as retail sales and food services, will generate large numbers of net new growth. The changing pattern of occupational employment has implications for education and training.